Clinical significance of upper airway dysfunction in motor neurone disease. Issue 9 (September 1994) - García-Pachón, E; Martí, J; Mayos, M; Casan, P; Sanchis, J
Abstract : BACKGROUND--To assess the occurrence, functional characteristics and prognostic value of upper airway dysfunction in motor neurone disease, 27 patients unselected for respiratory symptoms were studied. METHODS--Upper airway function was evaluated by analysis of the maximal flow-volume loop. Neurological diagnosis was established from the clinical history and physical examination. The degree of impairment was quantified by the Appel score. RESULTS--Twelve patients (group A) showed abnormalities of the maximal flow-volume loop consistent with flow limitation (seven patients) or instability of upper airway function (gross oscillations of airflow, five patients). The remaining 15 patients (group B) exhibited a normal or generally reduced maximal flow-volume loop, suggestive of muscle weakness. No differences were observed between groups in general physical condition, rate of disease progression, or duration of disease. CONCLUSIONS--Upper airway dysfunction in patients with motor neurone disease was a frequent finding. It was present more often, but not exclusively, in patients with bulbar features and was unrelated to prognosis.